Mobile Phishing Websites Detection and Prevention Using Data Mining Techniques - Kadhim, Huda Yousif; Al-saedi, Karim Hashim; Al-Hassani, Mustafa Dhiaa (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Abstract— The widespread use of smart phones nowadays makes them vulnerable to phishing. Phishing is the process of trying to steal user information over the Internet by claiming they are a trusted entity and thus access and steal the victim’s data(user name, password and credit card details). Consequently, the need for mobile phishing detection system has become an urgent need. And this is what we are attempting to introduce in this paper, where we introduce a system to detect phishing websites on Android phones. That predicts and prevents phishing websites from deceiving users, utilizing data mining techniques to predict whether a website is phishing or not, relying on a set of factors (URL based features, HTML based features and Domain based features). The results shows system effectiveness in predicting phishing websites with 97% as prediction accuracy.